2021
DOI: 10.3390/nu13114182
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Metabolic Syndrome Is Affected by Length of Daily Siesta: Results from a Prospective Cohort Study

Abstract: Background: Siesta has been associated with increased incidence of cardiovascular disease but the mechanism remains unclear. New studies into the relationship between siesta and metabolic syndrome have identified siesta length as a crucial differential, suggesting that siesta less than 40 min is associated with decreased risk of metabolic syndrome, while longer siesta is associated with increased risk. We aimed to investigate the effect of siesta duration on development of metabolic syndrome in a Mediterranean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
4
0
1
Order By: Relevance
“…In agreement with previous studies [13,16,17], our data showed that long siestas were associated with higher values of obesity-and MetS-related traits, particularly BMI, waist circumference, glucose, and blood pressure (SBP and DBP), as compared with no siesta, whereas short siestas were nominally associated with lower values of SBP and with a significantly lower prevalence of elevated blood pressure, i.e., SBP ≥ 120 mm Hg (cutoff point for "elevated" blood pressure) [25].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous studies [13,16,17], our data showed that long siestas were associated with higher values of obesity-and MetS-related traits, particularly BMI, waist circumference, glucose, and blood pressure (SBP and DBP), as compared with no siesta, whereas short siestas were nominally associated with lower values of SBP and with a significantly lower prevalence of elevated blood pressure, i.e., SBP ≥ 120 mm Hg (cutoff point for "elevated" blood pressure) [25].…”
Section: Discussionsupporting
confidence: 93%
“…Among habitual nappers (i.e., on average, those who take a siesta at least once per week during weekdays), the question “What is the duration in minutes?” allowed us to quantify habitual siestas and to categorize as follows: 1 = short siesta; and 2 = long siesta, ≤30 and >30 minutes, respectively. A short siesta was defined as ≤30 minutes based on previous studies [16, 17, 26].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existen distintos factores que han demostrado tener un papel en la génesis del SM: la obesidad 167 , el peso al nacer 168 , algunas endocrinopatías 169 , la esteatohepatitis grasa no alcohólica 170 171 , la elevación de la proteína C reactiva y sustancias pro inflamatorias en sangre 172 , la edad , la depresión 173 174 , el estrés emocional 175 , el estado civil 176 , el nivel socioeconómico 177 , la raza 178 , factores genéticos 179 180 y factores modificables como la dieta 181 121 182 119 120 121 , la AF 181 , el sedentarismo 183 , el consumo de tabaco 184 , el consumo de alcohol 185 , las horas de sueño 186 187 y la siesta prongada 188 . Todos ellos contribuyen a la aparición de los dos componentes principales del SM: la obesidad central y la resistencia a la insulina.…”
Section: 62 Factores De Riesgo Del Síndrome Metabólicounclassified